Tinjauan Viktimologi terhadap Tindak Pidana Pembunuhan : Studi Kasus Putusan Nomor 448/Pid.B/2023/PN Serang (International Forum of Researchers and Lecturers, 2025)
Murder has a major impact on the victim and his family in terms of psychology, social, and economics. Therefore, it is only right that the victim and his family are given protection and equal attention as given to the perpetrator in the judicial process. However, in practice, the criminal justice system is still focused on the perpetrator and the criminalization process while the rights and attention of the victim and his family tend to be sidelined. This study aims to analyze the psychosocial impact on the victim and his family and the extent to which the guarantee and implementation of the protection of the victim's rights related to the case in Decision Number 448/Pid.B/2023/PN Serang. The method used in this study is empirical yuridical based on data obtained directly through interviews. The results of this study indicate that the victim's family from the case in Decision Number 448/Pid.B/2023/PN Serang experienced long-term psychological trauma, social stigma against the victim's partner because of the case's connection to infidelity, and economic difficulties due to the loss of the main source of income. In addition, there is also fear and insecurity about the occurrence of similar crimes in society. During the judicial process, the position of the victim and his/her family is merely an instrument needed to ensnare the perpetrator while their rights such as financial compensation, mental rehabilitation, and legal protection tend to be ignored. A more significant role for the victim as a subject entitled to recovery and legal protection will reflect a just and humane criminal justice system.